Excess mortality and the COVID-19 pandemic: causes of death and social inequalities - Jieun Oh; Jieun Min; Cinoo Kang; Ejin Kim; Jung Pyo Lee; Ho Kim; Whanhee Lee (BMC, 2022)
Abstract Background During the coronavirus diseases 2019 (COVID-19) pandemic, population's mortality has been affected not only by the risk of infection itself, but also through deferred care for other causes and changes in lifestyle. This study aims to investigate excess mortality by cause of death and socio-demographic context during the COVID-19 pandemic in South Korea.  Methods Mortality data within the period 2015-2020 were obtained from Statistics Korea, and deaths from COVID-19 were excluded. We estimated 2020 daily excess deaths for all causes, the eight leading causes of death, and according to individual characteristics, using a two-stage interrupted time series design accounting for temporal trends and variations in other risk factors. Results During the pandemic period (February 18 to December 31, 2020), an estimated 663 (95% empirical confidence interval [eCI]: -2356-3584) excess deaths occurred in South Korea. Mortality related to respiratory diseases decreased by 4371 (3452-5480), whereas deaths due to metabolic diseases and ill-defined causes increased by 808 (456-1080) and 2756 (2021-3378), respectively. The increase in all-cause deaths was prominent in those aged 65-79 years (941, 88-1795), with an elementary school education or below (1757, 371-3030), or who were single (785, 384-1174), while a decrease in deaths was pronounced in those with a college-level or higher educational attainment (1471, 589-2328). Conclusion No evidence of a substantial increase in all-cause mortality was found during the 2020 pandemic period in South Korea, as a result of a large decrease in deaths related to respiratory diseases that offset increased mortality from metabolic disease and diseases of ill-defined cause. The COVID-19 pandemic has disproportionately affected those of lower socioeconomic status and has exacerbated inequalities in mortality.